(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
Speech is an essential communication tool that shapes how individuals perceive, interpret, and interact with the world around them. In the realm of education, speech plays a pivotal role in fostering academic cognition, as it facilitates the development of critical thinking skills, enhances comprehension and learning, and promotes creativity and social engagement. This article explores the multifaceted significance of speech in improving students’ academic cognition, emphasizing its integration within pedagogical approaches as a means to optimize educational outcomes.